NEW TENDENCIES IN PUBLIC PROCUREMENT – A WAY TOWARDS LEVELLING PLAYING FIELD OR A GLIMPSE OF PROTECTIONISM? (EU and comparative law issues and challenges series (ECLIC), 2021)
The purpose of this paper is to present the White Paper on levelling the playing field as regards foreign subsidies, from the public procurement perspective. This is the first time that the problem of foreign subsidies within public procurement is approached by European Commission and it is useful to analyse Commission’s findings on that regard. Due to the problems caused by COVID-19 pandemic and the forthcoming Next Generation EU initiative, the Commission is determined to develop and implement suitable legal instruments for dealing with distortions in  the Internal Market, caused by foreign subsidies. Legal analysis within the paper is focused on the proposed Module 3 under the White Paper, trying to detect possible practical repercussions of implementing measures as are proposed in the White Paper. In addition, the paper seeks to identify primary function of the measures proposed and tries to examine if that function could result in protectionist effects.